Peran Pemuda dalam Pengembangan Wisata Pantai Lowita di Kabupaten Pinrang, Kasus: Pemanfaatan Media Sosial - Bulan Suci Ramadhani (Yayasan Literasi Sains Indonesia, 2022)
Youth is the mobilizer of the realization of sustainable tourism. The aims of the research is determine (1) the role of youth in the development of Lowita Beach tourism, and (2) the efforts to use social media asyouth publication rooms in development of Lowita Beach tourism. This research was conducted in Tasi’Walie Village, Suppa District, Pinrang Regency. The sample was selected using Porpositive Sampling and Snowbaliing Technique. The data were obtained through direct obseravation in Lowita Beach Tourism, Tasi’ Walie Village, interview to village head, PokDarwis head, youth mobilizers, youth, community leadears, villa manager, the staff Tourism Service, Youth, and Sport of Pinrang Regency, researchers and implementer of Lowita Area Development Program Pinrang Shrimp Eco-Farming Park and tourists, documentation study, and library study. The data were analysed using Descriptive Qualitative Method. The results of the research indicated that 1) the roles of village youth in the effort to beach tourism development are to participate in keeping the beach clean, to conserve and rehabilitate mangrove, to make use of sea waste to make crafts, to make use of tourism potencial as a business opportunity by building tourism cafe and tourist shirts, to participate in empowerment/training activities to make souvenirs and various types of processed foods, and to make promotional efforts, and (2) village youth are active to make publication efforts to promotre Lowita Beach tourism through uploading photos or videos to social media.